Further increase in the possible applications using AI with ROSES, our system for endovascular treatment - Danieli, Guido; De Rosa, Salvatore; Di Benedetto, Olindo; Greco, Pasquale F.; Indolfi, Ciro; Larocca, Gabriele; Loizzo, Stefano; Massetti, Massimo; Tinelli, Emanuele; Tinelli, Giovanni; Sabatini, Umberto; Tshomba, Yamume (Mechanical Engineering Advances, 2025)
ROSES (Robotic System for Endovascular Surgery) continuously measures the resistance encountered by a catheter during advancement without requiring additional specialized components. The system consists of up to six robotic actuators arranged linearly on slides that move along an inclined rail toward the patient. The final slide accommodates the sixth actuator, which houses four stepper motors, allowing for adjustments in the relative positions of the actuators. The proximal actuator is affixed to the last slide using side bars. A force transducer, connected to the motorized slide by a wire, measures the gravitational component of any object on the rail, which remains constant as the actuators move. However, if an external obstruction hinders catheter or guidewire progression, the force changes, triggering an alert. The system also facilitates the introduction of the first catheter, even if pre-curved, enabling complete separation between the surgeon and the patient throughout the entire procedure. ROSES employs compact, purely mechanical, disposable components compatible with commercially available catheters and guidewires, making it suitable for a wide range of interventions, including cerebral arterial procedures, aneurysm treatment, ischemic interventions, angioplasty, Transcatheter Aortic Valve Implantation (TAVI), and various lower and upper limb surgeries. Future enhancements include AI-assisted brain endovascular treatments and the integration of animated catheters capable of shape adaptation via console control. By recording console inputs, resistance forces, device penetration lengths, and X-ray images, ROSES effectively functions as the “black box” of endovascular surgeries. The system is protected by multiple pending international patent applications.